2021
DOI: 10.3390/s21041374
|View full text |Cite
|
Sign up to set email alerts
|

Feature Subset Selection for Malware Detection in Smart IoT Platforms

Abstract: Malicious software (“malware”) has become one of the serious cybersecurity issues in Android ecosystem. Given the fast evolution of Android malware releases, it is practically not feasible to manually detect malware apps in the Android ecosystem. As a result, machine learning has become a fledgling approach for malware detection. Since machine learning performance is largely influenced by the availability of high quality and relevant features, feature selection approaches play key role in machine learning base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The proposed framework extracted the malicious information and fed it to the blockchain by utilizing a classification algorithm, and consequently, improving the efficiency of the malware classification process since all the malicious information is stored in the blockchain. An additional proposed framework that uses the machine learning approach was proposed by [ 26 ]. The authors developed a subset of features based on examining the performance of various feature selection algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed framework extracted the malicious information and fed it to the blockchain by utilizing a classification algorithm, and consequently, improving the efficiency of the malware classification process since all the malicious information is stored in the blockchain. An additional proposed framework that uses the machine learning approach was proposed by [ 26 ]. The authors developed a subset of features based on examining the performance of various feature selection algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality features are crucial for building effective machine learning-based classification models. The opcode sequence is used effectively in malware detection, but if there are too many features leads to the model complexity and the "curse of dimensionality" problem will occur [8]. In addition to that, data normally contains significant noises and irrelevant features that add little or no value to the performance of the learning algorithms.…”
Section: Static Feature Selection For Iot Malware Detectionmentioning
confidence: 99%
“…Today, feature selection approaches are organized into filters, wrapper, embedded and hybrid methods. The filter methods select a subset of features without altering their original representation [20]. This method is used in many machine learning models because it is not constrained by any machine learning method.…”
Section: B Opcode Feature Selectionmentioning
confidence: 99%
“…The feature Subset Selection for Malware Detection in Smart IoT Platforms was developed by Abawajy et al 35 This approach utilized Chi‐squared technique, Naive Bayes approach for extraction of features. Accuracy, f‐measure, precision, recall, percentage of permissions were the performance measures employed and the analysis revealed that the accuracy rate was high with enhanced detection rate.…”
Section: Review Of Related Workmentioning
confidence: 99%